Contextual factors for the successful implementation of self-management interventions for chronic diseases: A qualitative review of reviews - Noordman, Janneke; Meurs, Maaike; Poortvliet, Rune; Rusman, Tamara; Orrego-Villagran, Carola; Ballester, Marta; Ninov, Lyudmil; de Guzmán, Ena Niño; Alonso-Coello, Pablo; Groene, Oliver; Suñol, Rosa; Heijmans, Monique; et al. (Chronic illness, 2024)
To identify and describe the most relevant contextual factors (CFs) from the literature that influence the successful implementation of self-management interventions (SMIs) for patients living with type 2 diabetes mellitus, obesity, COPD and/or heart failure. We conducted a qualitative review of reviews. Four databases were searched, 929 reviews were identified, 460 screened and 61 reviews met the inclusion criteria. CFs in this paper are categorized according to the Tailored Implementation for Chronic Diseases framework. A great variety of CFs was identified on several levels, across all four chronic diseases. Most CFs were on the level of the patient, the professional and the interaction level, while less CFs were obtained on the level of the intervention, organization, setting and national level. No differences in main themes of CFs across all four diseases were found. For the successful implementation of SMIs, it is crucial to take CFs on several levels into account simultaneously. Person-centered care, by tailoring SMIs to patients' needs and circumstances, may increase the successful uptake, application and implementation of SMIs in real-life practice. The next step will be to identify the most important CFs according to various stakeholders through a group consensus process.